Meneladani Akhlak Rasululloh Melalui Program Syahrul Quran Di Pesantrean - Robbaniyah, Qiyadah (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2023)
Al-Quran learning in Islamic boarding schools makes it possible to implement Al-Quran Moral Practices by knowing the morals of Rasulullah and applying them in daily activities, so researchers are interested in digging deeper into how to emulate the Morals of Rasulullah through learning Al-Quran in Islamic boarding schools, where the research is conducted. Bin Baz Yogyakarta Islamic Center. Qualitative research methods, data collection by interview, observation and documentation. The results of the study found that the Bin Baz Islamic Center Islamic Boarding School in familiarizing the morals of the Koran by imitating the Messenger of Allah has a Syahrul quran program, programs that run in the special month of Ramadan are designed and designed from the vision and mission, targets to be achieved, activities to be carried out, and schedules activity. The focus in Syahrul Quran activities is memorizing the Koran, getting to know the biography of Rasulullah, biography of Ulama and Qura`, memorizing asmaul husna, and practicing the morals of the Koran namely faith, piety, honesty, istiqomah, patience and gratitude in all activities. These programs aim to increase love and skills in learning the Qur'an and instill moral values and emulate the Prophet as the main role model.